A nationwide cross-sectional study of 15,611 lesbian, gay and bisexual people in China: disclosure of sexual orientation and experiences of negative treatment in health care - Yiu-tung Suen; Randolph Chun Ho Chan (BMC, 2020)
Abstract Background Lesbian, gay and bisexual (LGB) people often face individual- and system-level barriers in health care. However, LGB people's experiences of health care in non-European and non-American settings have been scarcely studied. In China, while it has been estimated that there are at least 70 million gender and sexual minorities, there has been no larger-scale study on LGB people's experiences of health care beyond a focus on gay men and HIV. This study is the first larger-scale quantitative study to investigate LGB people's experiences of health care in China, where non-heterosexuality is officially silenced and the needs of non-heterosexual people are largely ignored by service providers. Methods An online survey was designed in joint partnership by academic, community groups and the United Nations Development Programme. Targeted and snowball sampling was adopted for participant recruitment. Such unique cross-sectoral partnership made this research possible in the authoritarian state of China where data collection on LGB people is extremely rare. For the analysis in this paper, a sample of 15,611 Chinese LGB people were included. Frequency and descriptive statistics were conducted to describe the LGB respondents' demographic characteristics and their experiences in health care settings. Chi-square tests were conducted to test how experiences vary across LGB people with different demographic characteristics. Results More than three quarters of the respondents said they would be willing to disclose to their medical care providers their sexual orientation if asked. However, only 5.7% of the respondents said that medical care providers ever asked them about their sexual orientation. About 8.0% of the LGB people surveyed reported having experienced negative treatment in medical care settings. Six percent (5.7%) of the Chinese LGB people said in accessing mental health care services, they were recommended, coaxed into, or provided conversion therapy for sexual orientation, gender identity or gender expression. Conclusions There is a strong need to enhance LGB cultural competence among health care providers. Policymakers in China should also formulate laws, policies, regulations, clearly articulated codes of conduct, and transparent procedures and practices to ensure non-discrimination of LGB people in the health care system, with a particular focus on banning conversion therapy.